GAMBARAN VARIASI TERAPI GLAUKOMA PADA PENDERITA GLAUKOMA DI RSUD MEURAXA - Niska Alfisyahrin; Feriyani Feriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Glaucoma is a disease of pressure in the eyeball or intraocular pressure is increased due to the failure of the aquacous humor discharge. Glaucoma is the second leading cause of blindness worldwide. According to World Health Organization (WHO) data in 2010, an estimated 39 million people worldwide suffer from blindness and 3.2 million people are caused by glaucoma. Based on the results of the Basic Health Research in 2012, the prevalence of blindness based on the measurement of visus 3/60 in Indonesia is 0.9%, whereas respondents who have been diagnosed glaucoma by health personnel (4.6 ‰), one of Aceh province (12.8 ‰). Intraocular pressure is the only manageable risk factor to prevent blindness so that proper initial therapy can reduce the rate of blindness caused by glaucoma. The purpose of this study was to determine the therapy given to patients with glaucoma in Eye Poly Meuraxa Hospital 2016. This type of research is a descriptive study with a retrospective design. The sample of this study were patients diagnosed with glaucoma and treated by ophthalmologists. This study was conducted in May-June 2017. The sample size is 57 people and has met the study criteria. The data is presented in the form of frequency distribution table and determined percentage. From the results of the study, Beta Blocker was 50.5%, 25.3% Lipid Receptor Aginos, and 24,2% of Sostemic anhydrase inhibitor carbon. It can be concluded that beta- blocker therapy is higher than that of systemic carbonic anhydrase inhibitor and lipid-agonist receptor. And the provision of combination therapy is more frequently applied than with single therapyKeywords: Glaucoma, Glaucoma Therapy, Beta Blocker